Contrasting latitudinal patterns in diversity and stability in a high‐latitude species‐rich moth community. Issue 5 (19th February 2020) - Antão, Laura H.; Pöyry, Juha; Leinonen, Reima; Roslin, Tomas
Abstract: Aim: Biodiversity is currently undergoing rapid restructuring across the globe. However, the nature of biodiversity change is not well understood, as community‐level changes may hide differential responses in individual population trajectories. Here, we quantify spatio‐temporal community and stability dynamics using a long‐term high‐quality moth monitoring dataset. Location: Finland, Northern Europe. Time period: 1993–2012. Major taxa studied: Nocturnal moths (Lepidoptera). Methods: We quantified patterns of change in species richness, total abundance, dominance and temporal variability at different organizational levels over a 20 year period and along a latitudinal gradient of 1, 100 km. We used mixed‐effects and linear models to quantify temporal trends for the different community and stability metrics and to test for latitudinal (or longitudinal) effects. Results: We found contrasting patterns for different community metrics, and strong latitudinal patterns. While total moth abundance has declined, species richness has simultaneously increased over the study period, but with rates accelerating with latitude. In addition, we revealed a latitudinal pattern in temporal variability—the northernmost locations exhibited higher variability over time, as quantified by both metrics of richness and aggregated species population trends. Main conclusions: When combined, our findings likely reflect an influx of species expanding their ranges poleward in response to warming. The overall decline in abundance and the latitudinal effect on temporal variability highlight potentially severe consequences of global change for community structure and integrity across high‐latitude regions. Importantly, our results underscore that increases in species richness may be paralleled by a loss of individuals, which in turn might affect higher trophic levels. Our findings suggest that the ongoing global species redistribution is affecting both community structure and stability over time, leading to compounded and partly opposing effects of global change depending on which biodiversity dimension we focus on.